2021
DOI: 10.1007/s10072-021-05461-2
|View full text |Cite
|
Sign up to set email alerts
|

Delirium in COVID-19 patients: a multicentric observational study in Italy

Abstract: Introduction Although recent data show that SARS-CoV-2 infection seems to affect the central nervous system (CNS), little is known about the neuropsychiatric effects resulting from this condition. In addition to the well-known neurotrophism of coronaviruses, recent evidence shows also that the “cytokine storm” induced by the infection is at the basis of the neuroinflammation of the CNS. Furthermore, prolonged hospitalization, polypharmacotherapy, and isolation could be at the basis of the onset of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
11
0
1
Order By: Relevance
“…While in the present study, the frequency of delirium in 309 patients with confirmed COVID‐19 was determined. In addition, the measurement tool of that study for delirium was the 4 ‘A's Test, which only takes a few minutes, but in the present study, more reliable tools were used 28 . Moreover, another retrospective study was conducted in elderly patients with COVID‐19 in London, and the frequency of delirium in that population was 23.9%.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…While in the present study, the frequency of delirium in 309 patients with confirmed COVID‐19 was determined. In addition, the measurement tool of that study for delirium was the 4 ‘A's Test, which only takes a few minutes, but in the present study, more reliable tools were used 28 . Moreover, another retrospective study was conducted in elderly patients with COVID‐19 in London, and the frequency of delirium in that population was 23.9%.…”
Section: Discussionmentioning
confidence: 72%
“…In addition, the measurement tool of that study for delirium was the 4 'A's Test, which only takes a few minutes, but in the present study, more reliable tools were used. 28 Moreover, another retrospective study was conducted in elderly patients with COVID-19 in London, and the frequency of delirium in that population was 23.9%. In the limitations of their study, the authors mentioned that the retrospective nature makes the data interpretation to be done with caution.…”
Section: Logistic Regression Models For Predictors Of Frequency Of De...mentioning
confidence: 99%
“…Although the study design did not allow for a comparison with patients without corticosteroids, this prevalence appears important. Delirium, the most frequent complication reported in our cohort, is known to be associated with mortality in COVID-19 ( 37 ) and the severity of delirium increases with age and corticosteroid use ( 38 ). Secondary infections were reported in 7% of patients hospitalized for COVID-19 ( 39 ) but concerned 32.7% of our patients who received corticosteroids.…”
Section: Discussionmentioning
confidence: 92%
“…Após a análise dos resultados (Tabela 1), confirma-se que são fatores de risco não modificáveis para o delirium: sexo masculino, ser idoso, o número total de medicamentos em uso e uso de antipsicóticos, além de possuir demência e/ou deficiência auditiva, visual e funcional. Também pode estar associado a resultados clínicos ruins, incluindo a permanência hospitalar prolongada, admissão em institutos de longa permanência, necessidade de terapia intensiva, o uso de ventilação mecânica e a perda de independência (García-Grimshaw et al, 2020;Mcloughlin et al, 2020;Mattace-Raso et al, 2020;Duggan;Martinotti et al 2021).…”
Section: Discussionunclassified